Aspectos microbiológicos do sistema água residuária da suinocultura-solo - Moura, Alexandre Carvalho de (2015)
wastewater use in agricultural soils has been adapted as an important pratice for agriculture. Due to the reduction of the availability of the quality of water resources is becoming increasingly important to add value to the use of water. The swine wastewater is rich in organic matter, composed of various elements of chemical origin, physical and biological. Its addition in soil and water resources without previous studies and knowledge of its components, can cause changes in the soil, contamination of surface and groundwater, biology changes in these environments, as well as the contribution and accumulation of groups of microorganisms in the environment, including pathogens. Most studies on swine wastewater, mainly in Brazil, are restricted to its physical and chemical components, evaluating its impact directly on the ground, water bodies or in plant productivity. Few studies focus on the microbial composition of this type of waste and especially on the risk of environmental contamination by pathogenic microorganisms or even on the impact of this element in the soil microbial community. Thus these animal manure may have an important role as initiators of infectious diseases in animals and humans. Thus, this thesis consists of two papers. In the first article, a study was done to check the bacterial composition present in swine wastewater, and to verify the possibility of eliminating these microorganisms through the main anaerobic treatment systems used in Brazil. It was evaluated in particular pathogenic microorganisms of gastrointestinal origin of the pigs and microbial environmental markers. The wastewater samples were taken from pig farms that use bio-manure storage tanks and digesters as treatment methods for the waste. The results clearly showed the presence of biomarkers and pathogens in swine wastewater. Despite the possibility of decrease of certain microbial groups throughout the stages of the treatment process, no elimination of pathogens in either treatment systems. Thus, demonstrates the possibility of the spread of pathogens and microorganisms in the environment. In the second paper, the objective was to evaluate the effect of application of swine wastewater associated with mineral fertilizer in agriculture, after a long time of application of swine wastewater in the soil microbial community. Thus, samples were collected from soils after 18 production culture cycles, with the application of wastewater from pig farms and assessed the quantitative effects (basal respiration, microbial biomass and metabolic quotient) and qualitative (DGGE, biodiversity indices, correlation between the chemical conditions and soil microbial activity) in the soil microbial community. The results showed that the application of swine wastewater, especially after long time and in higher concentrations, can change the dynamics of soil microbial community, impacting the dump site. The results of these studies show the need for further studies to apply this type of waste in agricultural soils, in order to minimize the risk of environmental contamination and/ or spread of pathogens.